Productivity under large pay increases: Evidence from professional baseball - Kerry L. Papps (Institute for the Study of Labor (IZA), 2010)
The establishment of the free agency system in the 1970s resulted in large salary increases among professional baseball players. Historical data show that players have tended to perform better at early stages of their careers since free agency was introduced. Under the current salary bargaining system, players only become eligible for salary arbitration and free agency at predetermined points in their careers, resulting in sudden changes in salary growth rates at these points. Using data on official days of major league service, it is found that players with high expected salary growth perform better, consistent with efficiency wage theory.
urn:nbn:de:101:1-201010133151
Keywords: J24; J31; 330; efficiency wages; productivity; baseball